2014
DOI: 10.1007/s00253-014-5752-1
|View full text |Cite
|
Sign up to set email alerts
|

Preventing non-alcoholic fatty liver disease through Lactobacillus johnsonii BS15 by attenuating inflammation and mitochondrial injury and improving gut environment in obese mice

Abstract: The increasing prevalence of obesity worldwide is associated with a parallel increase in non-alcoholic fatty liver disease (NAFLD). To investigate the effect of Lactobacillus johnsonii BS15 on NAFLD, 120 male ICR mice were randomly divided into four groups and administrated with BS15 (2 × 10(7) cfu/0.2 mL or 2 × 10(8) cfu/0.2 mL) or phosphate buffered saline (PBS) throughout a 17-week experimental period. The mice were fed with normal chow diet (NCD) 5 weeks before the experimental period. Afterward, with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
105
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 36 publications
12
105
0
Order By: Relevance
“…The presence of a population of neomycin-sensitive gut bacteria and its association with obesity-related traits (figure 4D) suggests a potential beneficial interplay between these bacteria and energy regulation and metabolism. In the present study, H1 treatment did not affect the level of known commensal bacteria that possess anti-obesogenic properties, such as A. muciniphila ,23 56 L. reuteri 57 or L. johnsonii 58 (figure 4C). Further study of the functional gut microbiota and examination of their mechanism of action will be required to identify new strategies to prevent and treat obesity and related metabolic disorders 59…”
Section: Discussionmentioning
confidence: 42%
“…The presence of a population of neomycin-sensitive gut bacteria and its association with obesity-related traits (figure 4D) suggests a potential beneficial interplay between these bacteria and energy regulation and metabolism. In the present study, H1 treatment did not affect the level of known commensal bacteria that possess anti-obesogenic properties, such as A. muciniphila ,23 56 L. reuteri 57 or L. johnsonii 58 (figure 4C). Further study of the functional gut microbiota and examination of their mechanism of action will be required to identify new strategies to prevent and treat obesity and related metabolic disorders 59…”
Section: Discussionmentioning
confidence: 42%
“…Genes of lipid synthesis (PPARγ, DHCR24, PPARβ), lipolysis (HMGCS2, CAT I), and energy metabolism (PPARα) are involved in lipid metabolism. The obese mice induced by the HFD have association with abnormal lipid metabolism in the liver, including altered acetyl-CoA carboxylase 1 (ACC1), fatty acid synthetase (FAS), fasting-induced adipose factor (FIAF), and PPARγ gene expression (Kang et al, 2013;Xin et al, 2014). In our study, HFD also induced abnormal lipid metabolism compared with mice fed a normal diet (data not shown), including the up-regulation of lipid synthesis genes and downregulation of lipolysis.…”
Section: Discussionmentioning
confidence: 54%
“…So we conjecture that the lower body weight gain caused by B10 was due to its modulation of lipid metabolism other than because of different food intake or digestion. In recent years, numerous investigations have shown that probiotics can be considered as biotherapeutics in treating abnormal lipid metabolism Xin et al, 2014). In our study, hepatic TC, TG and serum HDL-C, glucose, activities of GOT and GPT are much less than those of HFD-fed mice (Tables 3 and 4).…”
Section: Discussionmentioning
confidence: 66%
“…5b,c). As Lactobacillus can protect against NAFLD by attenuating inflammation in mice2425 and was most significantly influenced by overfeeding, we hypothesized that Lactobacillus could regulate the complement system through its metabolite, lactic acid. In line with the increased abundance of Lactobacillus in the intestines of the overfed versus normally fed geese, the plasma level of lactic acid was also significantly increased in the overfed geese at both day 7 and 14 of overfeeding (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that Lactobacillus is involved in carbohydrate metabolism44, lipid metabolism19 and the immune system24. Lactobacillus also plays a protective role in the development of fatty liver242545.…”
Section: Discussionmentioning
confidence: 99%